PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PREZI PADA MATA PELAJARAN IPS KELAS VII DI SMP NEGERI 25 PEKANBARU - Maesa Saputra; Suarman Suarman; Hardisem Syahbrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research have a purpose to implement the development and feasibility study of interactive learning media Prezi in social lesson.. The research method used is research and development (R&D) which adapts the Brog and Gall model which has been modified by Sugiyono. The research data was obtained through a questionnaire instrument used by validators of media experts, material experts and users (teachers) each as many as two people to provide an evaluation of the development of the media created. The results showed that after several revisions were carried out in accordance with the results of the validator's assessment, it was finally obtained that the Prezi interactive learning media, especially in social lessson was in the very good category and deserved to be used. Because this research has not been continued with a limited trial, the researcher gives suggestions to further researchers so that the results of the research are very useful and are expected to be carried out at the trial stage (implementation stage).Key Words: Media, Developing, Prezi